2018
DOI: 10.1055/s-0038-1669790
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of Suture Anchor versus Transosseous Tunnel Patellar Tendon Repair Techniques

Abstract: The objective of this study is to compare the cyclic loading strength and ultimate failure load in suture anchor repair versus transosseous tunnel repair of patellar tendons using a cadaver model. Twelve cadaveric patella specimens were used (six matched pairs). Dual-energy X-ray absorptiometry (DXA) measurements were performed to ensure equal bone quality among groups. All right knees were assigned to the suture anchor repair group ( = 6), whereas all left knees were assigned to the transosseous bone tunnel g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 47 publications
(45 reference statements)
2
36
1
Order By: Relevance
“…Our load-to-failure values for knotless anchor were lower than those reported by Bushnell et al; however, 4 Fiberwire sutures were used in that study, whereas we used a single suture tape for the anchor repairs in the current study. Interestingly, our values were higher than those reported by Sherman et al, 19 even though their study used 3 anchors versus 2 in our study. The main differences in this study are the use of suture tape as well as the knotless anchor fixation type of the tape versus a threaded corkscrew anchor.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…Our load-to-failure values for knotless anchor were lower than those reported by Bushnell et al; however, 4 Fiberwire sutures were used in that study, whereas we used a single suture tape for the anchor repairs in the current study. Interestingly, our values were higher than those reported by Sherman et al, 19 even though their study used 3 anchors versus 2 in our study. The main differences in this study are the use of suture tape as well as the knotless anchor fixation type of the tape versus a threaded corkscrew anchor.…”
Section: Discussioncontrasting
confidence: 84%
“…Lanzi et al 14 found that suture anchors (2.16 mm) had significantly less gap formation than transosseous sutures (5.71 mm) after 1000 cycles. Sherman et al 19 tested patellar tendon suture anchor repair versus transosseous repair, showing no difference in gapping at the end of their study (2.92 and 3.33 mm, respectively; P ¼ .120).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In addition to minimizing the surgical dissection required, equivalent biomechanical results have been linked to less gapping under cyclic load. 6 …”
mentioning
confidence: 99%